(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: to describe the evidences of the specialized care in the attention to the people with digestive fistulas, since these can cause complications of high gravity that prolong the time of hospitalization and it are related to important mortality rates. Methods: This is an integrative review with quantitative descriptive analysis.18 articles were found and submitted to systematic analysis. Results: The formation of digestive fistulas is related to a series of complications, such as sepsis and infections, metabolic and electrolytic disorders, nutritional disorders, the presence of skin lesions and feelings of fear and anxiety on the part of the patient. The care plan includes multidisciplinary care and follow-up of the stomatherapist nurse in directing and indicating conducts for effluent control and skin protection, odour control, as well as ensuring mobility and emotional support. Conclusion: It is necessary research aimed at the care of people with digestive fistulas and to establish the relationship between clinical practice and well structured studies.